2021
DOI: 10.3390/genes12081133
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of CHD8 in Neurodevelopment and Autism Spectrum Disorders

Abstract: Chromodomain-helicase-DNA-binding protein 8 (CHD8) has been identified as one of the genes with the strongest association with autism. The CHD8 protein is a transcriptional regulator that is expressed in nearly all cell types and has been implicated in multiple cellular processes, including cell cycle, cell adhesion, neuronal development, myelination, and synaptogenesis. Considering the central role of CHD8 in the genetics of autism, a deeper understanding of the physiological functions of CHD8 is important to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…These results may be caused by disease-specific genetic variants of CHD8 that is a huge difference from the ASD without any genetic variants or with undefined ones. CHD8 is a chromatin remodeling/modifier factor that plays a role in the transcription process required for brain development 11 . LINE-1 and Alu elements have an activation and a repressive chromatin mark that is bound by several chromatin remodeling/modifier factors 39 , 42 , 47 , 58 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results may be caused by disease-specific genetic variants of CHD8 that is a huge difference from the ASD without any genetic variants or with undefined ones. CHD8 is a chromatin remodeling/modifier factor that plays a role in the transcription process required for brain development 11 . LINE-1 and Alu elements have an activation and a repressive chromatin mark that is bound by several chromatin remodeling/modifier factors 39 , 42 , 47 , 58 .…”
Section: Discussionmentioning
confidence: 99%
“…People with 16p11.2del are usually characterized by developmental delay, intellectual disability, or ASD 9 . CHD8 is strongly associated with ASD and other neurodevelopmental disorders including schizophrenia and intellectual disability 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Signaling by NTRK1 (TRKA) [55], cardiac conduction [56], signaling by GPCR [57], immune system [58], cytokine signaling in immune system [59], interferon signaling [60] and toll-like receptor cascades [61] were responsible for development of PD. Recent studies have shown that EGR2 [62], WNT1 [63], ARC (activity regulated cytoskeleton associated protein) [64], CHRNA7 [65], SEZ6L2 [66], IL1RAPL2 [67], PER2 [68], PCDH19 [69], CNTNAP2 [70], SLC12A5 [71], CDK5 [72], ACTL6B [73], GABRD (gamma-aminobutyric acid type A receptor subunit delta) [74], CACNA1G [75], HTR2C [76], STX1A [77], ATP1A3 [78], RIMS3 [79], CNTNAP2 [80], CDH8 [81], SCAMP5 [82], SYNGR1 [83], ARHGEF9 [84], DLG3 [85], RBP4 [86], IL9 [87], S100A9 [88], HGF (hepatocyte growth factor) [89], C3 [90], FKBP5 [91], GABRE (gamma-aminobutyric acid type A receptor subunit epsilon) [92], NCKAP1L [93], PIK3CG [94], ITGB3 [95], ANXA1 [96], SYNE2 [97] and DBI (diazepam binding inhibitor, acyl-CoA binding protein) [98] were closely involved with the occurrence, development, and prognosis of autism spectrum disorder. EGR2 [99], ADCYAP1 [100], CHRNA7 [101], NRN1 [102], ETV5 [103], STXBP1 [104], CAMKK2 [105], VAMP2 [106], SYNGR1 [107], NOD2 [108], TLR2 [109], BRCA2 [110] and LEF1 [111] were previously reported to be critical for the development of bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Chromodomain-helicase-DNA-binding protein 8 (Chd8) is a transcriptional regulator (Weissberg & Elliott, 2021). It is involved in the regulation of the cell cycle, neuron development, myelination, synaptogenesis, and many other processes, and has been proven to be one of the genes most strongly related to autism (Hoffmann & Spengler, 2021).…”
Section: Chd8 Micementioning
confidence: 99%